MISCUE ANALYSIS IN READING ALOUD BY INDONESIAN ENGLISH FOREIGN LEARNER - Vidya Arisandi; Kelik Wachyudi (STKIP Siliwangi, 2017)
This Research deals with “Miscue Ananalysis in Reading Aloud By Indonesian EnglishForeign Learner.” This researchfocuses on diagnostics tool in reading by using miscueanalysis has been studied less extensively.The goal of this research is to check learners‟reading comprehension on text by using diagnostic tool. Therefore, this research isundertaken to investigate the features of miscues produced by the Indonesian EFL learnersin the process of orally reading English text. The method is focused to explicate participant,research data, research instruments, data collection and data analysis. There are variousmiscues occur in this study, such as mispronuncitaion, insertion, omission, calls for help,hesitation, repetition, and self correction. It can be concluded that Reading aloud can makelearners have good pronunciation. It means that their dialect can be corrected while they arereading aloud. Reading speed influences reading comprehension.Keywords: Miscue Analysis, Reading aloud and EFL